Some results on dynamics of fractional derivatives via difference sequences. (7th December 2020) - Baliarsingh, P.; Nayak, L.; Dutta, Hemen
Abstract : In this paper, we extend the applications of difference operators and related sequence spaces for the study of the fractional calculus and its dynamics. In this context, some useful results on dynamics of fractional derivatives have been established and demonstrated with the help of existing formulas. Particularly, this study suggests some basic reasons for dynamic behaviors of Riemann‐Liouville fractional derivatives and provides certain idea for neutralizing them.